Criminal Law Reform in Education Based on Human Rights: A Comparative Perspective - Astuti, Pudji; Konara, Thamasi (Universitas Negeri Semarang, 2025)
Educational criminal law aims to protect human rights for both teachers and students. This research aims to analyze the reform of criminal law in education by comparing the laws of Indonesia, Finland, and Egypt. This research is a normative legal study with a comparative, conceptual, and legislative approach. The novelty of this research lies in the substance of criminal law regulations in the field of education in Indonesia, which are still general, such as sanctions for teachers who commit molestation against students. The novelty of this research is that in Finland, the critical role of SOOL as a teacher professional organization is being implemented in cases involving teachers and students, and in Egypt, where criminal sanctions related to the abuse of authority in establishing higher education institutions are emphasized. The reform of criminal law in the field of education in Indonesia can be directed towards protecting teachers and involving teacher professional organizations to ensure that teachers cannot be criminally prosecuted for imposing disciplinary sanctions, while also guaranteeing student protection. This research recommends the need for specific regulations on criminal sanctions in the field of education in a separate special or sectoral law as a lex specialis of the New Criminal Code.